Determinants of Output and Profitability among Lowland Rice Producers in North West, Nigeria - Alabi, Olugbenga Omotayo; Aluwong, Jeremiah Samuel; Maharazu, Ibrahim; Mailumo, Sunday Sambo; Mohammed, Adam Abubakar; Ajibola, Akeem Olusola; Ocheni, Ademu (Nepalese Journal of Agricultural Sciences, 2025)
This work is centered on determinants of output and profitability analysis among lowland rice producers in North West, Nigeria. A multi-stage sampling design was utilized, at the fourth-stage, a random sampling approach was utilized to select 200 lowland rice producers. Primary data of cross-sectional sources were utilized for this research, the data were estimated utilizing descriptive statistics, farm budgetary method, and stochastic production frontier version. The result shows that approximately 78% of lowland rice producers were male with mean age of 42 years. They are small-scale producers with an average farm size of 1.27 hectares. The lowland rice production is profitable with an evaluated gross margin (GM) and net farm incomes of 916219.39 and 868078.35 Naira per hectare. The fertilizer usage, seed, farm size, agrochemicals, and labour were significant and positively affect the quantity of rice produced. The investigation recommends that credit at single interest rate should be giving to rice producers.